HunSum-1 an abstractive summarization dataset for Hungarian - Barta Botond; Lakatos Dorina; Nagy Attila; Nyist Milán Konor; Ács Judit; Magyar számítógépes nyelvészeti konferencia (19.) Szeged 2023. január 26-27. (2023)
We introduce HunSum-1 : a dataset for Hungarian abstractive summarization, consisting of 1.14M news articles. The dataset is built by collecting, cleaning and deduplicating data from 9 major Hungarian news sites through CommonCrawl. Using this dataset, we build abstractive summarizer models based on huBERT and mT5. We demonstrate the value of the created dataset by performing a quantitative and qualitative analysis on the models’ results. The HunSum-1 dataset, all models used in our experiments and our code1 are available open source.
Keywords: Természettudományok; Számítás- és információtudomány